Subsequent injuries and early recurrent diagnoses in elite Rugby Union players - Williams, S.; Trewartha, G.; Kemp, S.; Cross, M. J.; Brooks, J. H. M.; Fuller, C. W.; Taylor, A. E.; Stokes, K. A. (International Journal of Sports Medicine, 2017)
An eight-season (2005/06-2012/13) prospective cohort design was used to record time-loss injuries in 15 English Premiership teams. Data pertaining to a total of 1556 players and 9597 injuries (8180 subsequent) were included in the analysis. Injuries subsequent to an index injury were classified as (1) New: different site; (2) Local: same site (and different type); or (3) Recurrent: same site and type. The severity of subsequent injuries (days missed) was compared with their related index injury. The proportions of early (<2 months), late (2-12 months) and delayed (>12 months) subsequent injuries were compared across injury classifications and diagnosis groupings. The majority of subsequent injuries (70%) were classified as new injuries, with 14% local and 16% recurrent. A large proportion of recurrent subsequent injuries (42%) occurred within two months of return-to-play. Subsequent injuries were not more severe than their corresponding index injury (effect sizes <0.20). Specific local and recurrent subsequent injury diagnoses with the highest risk of occurring within two months of return-to-play were: `neck muscle strain`, `ankle joint capsule sprain`, and `cervical nerve root` injuries. These findings may be used to drive targeted secondary prevention efforts, such as reconsideration of return-to-play protocols for neck muscle strain injuries.